K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 7 2015

\(8^n:2^n=16^n\)

\(\left(2^3\right)^n:2^n=\left(2^4\right)^n\)

\(2^{3n}:2^n=2^{4n}\)

\(\Rightarrow3n-n=4n\)

\(\Rightarrow n\left(3-1\right)=4n\)

\(\Rightarrow n.2=4.n\)

\(\Rightarrow\)không có giá trị n

24 tháng 7 2015

\(8^n:2^n=16^n\Rightarrow2^{3n}:2^n=2^{4n}\Rightarrow2^{2n}=2^{4n}\)

=> 2n = 4n => n = 2n => n - 2n = 0 => n ( 1 - 2 ) = 0 => - n = 0 => n = 0 

4 tháng 9 2017

Ta có: 8: 2=23n:2n=23n-n=22n

162017=(24)2017=28068

 nên 22n=28068 nêm 2n=8068 nên n=4034

4 tháng 9 2017

=>82ko17x2;3;4;5;6;...;21;2;3;...=>{1;2;3;4;5;6;..}

3 tháng 7 2015

a)16/2n=2

=>16=2n.2

=>8=2n

=>23=2n

=>n=3

b)(-3)n/81=-27

<=>(-3)n=(-27).81

<=>(-3)n=-2187

<=>(-3)n=(-3)7

<=>n=7

c)8n:2n=4

<=>8n=4.2n

<=>23n=22+n

<=>3n=2+n

<=>2n=2

<=>n=1

17 tháng 8 2018

\(a,\frac{16}{2^n}=2\)

\(\Rightarrow\frac{16}{2^n}=\frac{2}{1}\)

\(\Rightarrow2^n.2=16\)

\(\Rightarrow4^n=4^2\)

\(\Rightarrow n=2\)

\(b,\frac{\left(-3\right)^n}{81}=-27\)

\(\Rightarrow\left(-3\right)^n=81.\left(-27\right)\)

\(\Rightarrow\left(-3\right)^n=-2187\)

\(\Rightarrow\left(-3\right)^n=\left(-3\right)^7\)

\(\Rightarrow n=7\)

17 tháng 8 2018

16/2^n=2 => 2^n .2 =16 => 2^n=8=2^3=>n=3

8 tháng 8 2016

a, \(\frac{16}{2^n}=2\)

\(\frac{2^4}{2^n}=2\)

24 : 2 = 2n

2= 23

n =3

b)   8n :2n =4

     (8:2)n  = 4

    4n      = 4

nên n = 1

5 tháng 2 2016

a. 1/8=2n:16n

1/8=1/8n

=>n=1

b.27<3n<243

<=>33<3n<35

=>n=4

9 tháng 3 2019

a) 1/8 . 16= 2n

    1/8          = 2: 16n

    1/8          = ( 2/16 )n

    1/8          = ( 1/8 )n

=> n = 1

b) 27 < 3< 243

    33 < 3n < 35

=> n = 4

a . 16 / 2^x = 2 

= > 16 : 2^x = 2 

=> 2^4 : 2^x = 2^1 

=> x = 3 

b . ( -3 )^x/ 81 = -27 

=> -3 ^ x = -27  . 81 

=  > -3^x = -2187

=> -3^ x = -3^7

=> x = 7 

c . 8^ x : 2^x = 4 

=> 4 ^ x = 4 

=> x = 1 

13 tháng 9 2016

a) 16/2^n = 2

       2^n  = 16 : 2

       2^n  = 8

       2^n  = 2^3

=>   n     = 3

b) (-3)^n/81 = -27

    (-3)^n     = 81 : (-27)

    (-3)^n     = -3

=> n = 1

c) 8^n : 2^n = 4

   (8 : 2)^n   = 4

      4^n       = 4

=> n = 1